LITERATURE REVIEW ANALYSIS FACTORS RELATED TO MATERNAL PRIMIGRAVIDA ANXIETY BEFORE CHILDBIRTH - Sinambela, Selpiana; Berutu, Clara Amelia; Senawati; Tarigan, Eka Falentina; Ginting, Astaria (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Anxiety before childbirth is common among pregnant women, and tends to be more pronounced in primigravida mothers who have no prior delivery experience. This paper attempts to summarize the factors associated with such anxiety, based on 16 research articles published between 2020 and 2025 and obtained through Google Scholar. Several factors appear repeatedly across the articles reviewed, including maternal age, gravida status, husband support in its various forms (informational, appraisal, instrumental, emotional), family support, religiosity, maternal knowledge about childbirth, ANC visit compliance, and the effect of childbirth-related health education. Among these factors, husband support was mentioned most frequently and tended to show a consistent relationship with anxiety levels across studies. Several experimental studies also showed that health education interventions could meaningfully reduce anxiety scores. Overall, this review suggests that strengthening support from husbands and families, combined with adequate health education and ANC compliance, are important steps in helping primigravida mothers face childbirth with greater calm.